Bridging the gap : disciplines, times, and spaces in dialogue.. Volume 1,, Sessions 1, 2, and 5 from the conference Broadening Horizons 6 held at the Freie Universitȧt Berlin, 24-28 June 2019 - Hess, Christian W.; Manuelli, Federico (2021)
Since 2007, the conferences organised under the title 'Broadening Horizons' have provided a regular venue for postgraduates and early career scholars in Ancient Near Eastern Studies. Three volumes present the proceedings of the 6th Broadening Horizons Conference, which took place at the Freie Universitt̃ Berlin from 24-28 June, 2019. The general theme, 'Bridging the Gap: Disciplines, Times, and Spaces in Dialogue', is aimed at encouraging communication and the development of multidisciplinary approaches to the study of material cultures and textual sources. Volume 1 contains 17 papers from Session 1: Entanglement. Material Culture and Written Sources in Dialogue; Session 2: Integrating Sciences in Historical and Archaeological Research; and Session 5: Which Continuity? Evaluating Stability, Transformation, and Change in Transitional Periods.